A business plan for NatCha, a specialty contemporary tea shop, to enter Malaysia’s F&B industry - Dechgan, Natcha (2020)
This report explains how NatCha is seeking to enter Malaysia’s Food & Beverages industry (F&B) as a specialty contemporary tea shop, whereby its unique selling points are the use of natural sweetener alternative – Stevia – and the application of cutting-edge technology in the production of its tea drinks.